Answer:
84
Step-by-step explanation:
First you multiply 2 and 7
Ans 14
Then you multiply 14 and 6
Ans 84
<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3
3 ( x ) + 55 = 85
Answer To Solving Y:
Let's solve your equation step-by-step.
3x + 55 = 85
Step 1: Subtract 55 from both sides.
3x + 55 − 55 = 85 − 55
3x = 30
Step 2: Divide both sides by 3.
3x / 3 = 30 / 3
x = 10
<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3
Answer To The Angle:
( 3 ) ( 10 ) + 55 = 85
<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3
2 ( y ) - 5 = 95
Answer:
Let's solve your equation step-by-step.
2y − 5 = 95
Step 1: Add 5 to both sides.
2y − 5 + 5 = 95 + 5
2y = 100
Step 2: Divide both sides by 2.
2y / 2 = 100 / 2
y = 50
<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3
Answer To The Angle:
( 2 ) ( 50 ) − 5 = 95
<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3
Please don't come at me if I am wrong.....:\
<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3
But, the anwer should be 180 degrees
Answer:
C
Step-by-step explanation:
Answer:
Step-by-step explanation:
x²- y² = (x+y) (x-y)
x² + xy = x(x+y)
x² + 2xy + y² = (x+y) (x+y)
7) Use distributive property
3x(4x⁴ - 5x)=3x*4x⁴- 3x*5x = 12x⁵ - 15x²
8) When you open parenthesis with minus sigh in front of it, you need change sings of the terms on opposite. Then find like terms.
(5x⁴-3x³+6x)-(3x³+11x²-8x)= 5x⁴-3x³+6x -3x³-11x²+8x =5x⁴-6x³ - 11x²+14x
9)(x-2)(3x-4)=x*3x-4x-6x+8=3x²-10x+8
10) (x+6)²=(x+6)(x+6)=x²+6x+6x+36=x²+12x+36
For (x+6)², you can also use the formula of the perfect square
(a+b)²=a²+2ab+b²
For (x+6)² =x²+2*x*6 +6²=x²+12x+36